Information about foregone rewards impedes dynamic decision-making in older adults. Issue 1 (2nd January 2016) - Cooper, Jessica A.; Worthy, Darrell A.; Maddox, W. Todd
Abstract : "Making an informed decision" implies that more information leads to better decisions, yet it may be the case that additional information biases decisions in a systematic and sometimes detrimental manner. In the present study, we examined the effect of additional information on older adults' decision-making using a task for which available rewards were dependent on the participant's recent pattern of choices. The optimal strategy was to forego the immediately rewarding option in favor of the option that yielded larger delayed reward. We found that providing information about true foregone rewards – the reward that would have been received had the participant chosen the other option – significantly reduced older adults' decision-making performance. However, false foregone rewards – foregone rewards manufactured to make the long-term option appear more immediately rewarding – led older adults to perform at a level equal to younger adults. We conclude that providing information about foregone rewards biases older adults toward immediate rewards at a greater rate than younger adults, leading to poorer older adult performance when immediate rewards and long-term rewards conflict, but intact performance when immediate rewards and long-term rewards appear to align.